Through the eyes of parents: Culture of young children in diverse early learning spaces - Van As, A.; Excell, L.; Magadala, N.; Gqoli, N. (My University, 2020)
There is a growing emphasis for early education to be both contextually appropriate and culturally responsive. In post-apartheid South Africa, early childhood care and education (ECCE) centres have become ‘melting pots’ of different cultures, reinforcing the call to become culturally relevant. Affirming each family’s cultural norms and values is pivotal in shaping the child’s identity – especially in a multicultural society. However, there exists an absence of research investigating how parents of young children view their families’ cultural norms and values. This phenomenologically qualitative study investigated parents’ understandings of culture and their cultural aspirations for their young children attending culturally diverse ECCE centres. One-on-one interviews were conducted to explore parents’ cultural narratives of how they view the cultural identities of their young children. Participants comprised 19 parents who were purposefully selected from five South African provinces. Findings revealed that parents were initially hesitant to articulate what culture in a democratic South Africa would look like. However, when they reflected on culture as enacted in the lives of their families they responded with conviction, revealing a range of views about the topic. They described how they experienced their culture through artefacts, language, family, religion and place. Parents recognised the valuable opportunities that the language-diverse ECCE spaces offered for mixing languages and developing bilingualism and multilingualism. The parents’ intuitive understandings of their children’s culture confirm that there are meaningful levels of cultural knowledge to be found at the grassroots level.